“Diseño e implementación de un deshidratador solar de chocho (lupinus mutabulis sweet), para el uso agroindustrial en la Universidad Técnica de Cotopaxi Area CEASA”. *Chocho (lupinus mutabulis sweet). - German Pila, Juan Fernando (2018)
The objective of this titling project was to implement a lupine dehydrator, based on solar energy for its operation, in the COTOPAXI TECHNICAL UNIVERSITY CEASA area (Experimental Salache Campus) and in this way improve the drying process and the quality of flour. of said product. The machine consists of three main parts, the collector where solar energy is captured, the drying chamber where the product to be dried is located, and the control system that allows temperature control. In the design of the dehydrator, a previous investigation was carried out to find the optimal working parameters. As a first part, all the information of the theoretical framework and the analysis of alternatives are detailed. The properties, characteristics of the product to be dried were determined, from which the alternatives are exposed, later the election, calculations and selection of the constituent elements of the machine were made. The respective process sheets for each of the elements are included, in addition to the respective plans necessary for its manufacture and assembly. Based on the design, a prototype of a solar dehydrator has been built and tests were carried out with chocho, with a solar catchment area of 22, and 8 of chocho, results have been obtained: average temperature in the drying chamber of 30 ° C, average temperature in the collector of 41.5 °C, average daily global solar radiation of 686 ⁄2, average forced wind speed of 2 3⁄, the reduction in moisture content is notable after 1680 min ( 28 h), having as a consequence the reduction of the average moisture content up to 0.4% of final moisture content, taking into account that the drying time depends on the amount of product that the producer wants to dry and the solar radiation incident on the product. place where the drying process of the raw material will proceed. The experimental analysis of lupine drying is presented, with a machine efficiency of 24%, and the costs related to the design and construction of the machine are detailed, reaching a total economic cost of $2,202.70 dollars.